Horsemen of terror - Jenkins, Jerry B.; Fabry, Chris, 1961-; LaHaye, Tim F. (Wheaton, Ill. : Tyndale House, 2002)
The young Tribulation Force, a group of teens left behind on Earth after God's Rapture, faces the prospect of being forced underground after the evil Global Community unleashes a plan to trap believers.
"The unseen judgment"--Cover.
"Tyndale Kids.".
5.8
5-8
Keywords: Christian fiction; Eschatology -- Fiction; Fantasy; Schools -- Fiction; Teenagers -- Fiction; Christian fiction; Eschatology -- Fiction; School stories; Teenagers -- Fiction; Fantastic fiction